A cross–cultural comparison of whistleblowing perceptions. (9th February 2015) - Cheng, Xintong; Karim, Khondkar E.; Lin, Karen Jingrong
Through an empirical examination, this research reports on the results of cultural influences on whistleblowing decisions and the perception of people from individualistic cultures and those from collectivist cultures. We utilise cultural differences and characteristics between different nations to formulate hypotheses that individuals from collectivist cultures are less likely to be whistle–blowers, and less accepting of whistleblowing behaviour, than individuals from individualistic cultures. Data were collected through a survey given to subjects of British and Chinese students from the University of Glasgow. The results support hypotheses about diversity in decisions made by individuals from individualistic cultures compared to those from collectivist cultures. The research findings have implications for the administration of domestic and multinational corporations. In order to enhance the effectiveness of internal control systems in various nations, such systems should take cultural differences into consideration. The results suggest that, compared to collectivist cultures, whistleblowing as an organisational strategy of internal control systems is more likely to be effective in individualistic cultures.